2022
DOI: 10.1101/2022.10.07.22280823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and facilitators to anti-retroviral therapy adherence among adolescents aged 10 to 19 years living with HIV in sub-Saharan Africa: A mixed-methods systematic review

Abstract: Background: Human Immunodeficiency Virus (HIV) significantly affects adolescents globally, with the sub-Saharan Africa (SSA) reporting a high burden of the disease. HIV testing, treatment, and retention to care are low among adolescents. We conducted a mixed-method systematic review to assess anti-retroviral therapy (ART) adherence; barriers and facilitators to ART adherence and ART outcomes among adolescents living with HIV and on ART in sub-Saharan Africa. Methods: We conducted searches in four scientific da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…For example, Muwanguzi et al, reported 65% among the adolescents and young people aged 15-24 years [5], 29% by Izudi et al, [21], 69.5% by Cluver et al, [7] and by Zanooni et al, 89% [22] and 35.7%, Nimwesigwa et al, [11]. As for VLS, it was higher than reported by Hlophe et al, [4] at 55%, 65% by Simms et al, [9], 62% in Kenya [23] but lower than by Tugume et al, [6] at 81%. However, it is important to note that the latter was based on a cut off of 1000 copies/mL rather than the 200 copies/mL used in this study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Muwanguzi et al, reported 65% among the adolescents and young people aged 15-24 years [5], 29% by Izudi et al, [21], 69.5% by Cluver et al, [7] and by Zanooni et al, 89% [22] and 35.7%, Nimwesigwa et al, [11]. As for VLS, it was higher than reported by Hlophe et al, [4] at 55%, 65% by Simms et al, [9], 62% in Kenya [23] but lower than by Tugume et al, [6] at 81%. However, it is important to note that the latter was based on a cut off of 1000 copies/mL rather than the 200 copies/mL used in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, The Joint United Nations Program Against HIV/AIDS (UNAIDS) estimates, indicated that the global VLS in the sub-population was at 46% during the same year. A recent systematic review in SSA, reported a 55% VLS among the ALHIV and 65% adherence [4]. Similarly, In Uganda,.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation